Nigeria : Country Financial Accountability Assessment - World Bank (Washington, DC, 2013)
The Federal Government of Nigeria retains the vestiges of good systems for planning, budgeting, managing and controlling public resources. But their performance has deteriorated to such an extent that they provide negligible assurance that moneys are used entirely for their intended purpose. The same is true at the state level. To return to an acceptable level of financial accountability will require sustained action over several years. In the interim, risks of waste, diversion and misuse of funds are assessed as high. This has clear implications for both Government and the Bank: the former needs to improve financial accountability along the lines outlined in this report; and the latter needs to support this process and in the meantime to build explicit risk minimization actions into all its Nigerian operations. Among the recommendations presented for the public sector are to address: the calculation, control, management, protection, reporting and disclosure of national oil revenues; the adequacy of procedures for drawing money from the Consolidated Revenue Fund and for ensuring that transactions on accounts held at the Central Bank are properly authorized, managed and audited; the legal provisions requiring the public disclosure of assets and other valuable interests of public officials and politicians and the recovery of public sector assets illegally acquired; implementation and enforcement of the Anti-Corruption Act; and the legal provisions and enforcement arrangements for combating money laundering including the adequacy of central bank controls over commercial banks. Among the recommendations made to improve private sector participation are to: conduct a review of corporate governance and private sector financial accountability along the lines of the King Committee in South Africa; update the Companies and Allied Matters Act so that it reflects such principles and strengthens company audit; accelerate the issuance of accounting standards in areas where there are none at present but are available under International Accounting Standards (IASs) promulgated by the International Accounting Standards Committee (IASC); establish monitoring and enforcement mechanisms to ensure that all listed companies comply with national and IASs. In this regard, there is need to sufficiently strengthen the NASB's technical and professional capabilities; and ensure that the procedures for filing company information and providing public access to it are adequate.